Rito teatro performance. Modesta proposta per un ritorno alle origini (Mantichora. Italian Journal of Performance Studies, 2020)
What in theatre overcomes itself, is precisely the human being: the unique value of his presence here and now. There is nothing like that and this definitely distinguishes theatre from the so called ‘mediascape’. Our proposal, in this essay, is, once again, to go back to the ritual origins of theatre in order to understand what is common between this aesthetic and the ethic human aspiration. It’s clear, in this perspective, what we owe it to Turner and Schechner’s work, but, beyond the cognitive turn simplification which seems to agree with these great scholars’ attempt, we need to clarify how the rite is, essentially, something related to the notion of sacred vocation. It is impossible to deny this difference - though, diachronically, theatre, at its best, always tries to glean it again.